KETERHUBUNGAN PERTUMBUHAN EKONOMI DAN KUALITAS TENAGA KERJA - Fernaldi Anggadha Ratno; Malik Cahyadin; Tamat Sarmidi (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
Economic growth can influence the quality of the workforce through the Solow economic model, the higher the quality of the workforce has implications for economic growth. Therefore, this research aims to estimate the relationship between workforce quality and economic growth in 7 Surakarta jurisdictions during 2019-2023. The research method uses panel data regression with a total of 6 districts and 1 city in Surakarta Residency including education, namely registered job seekers according to the highest level of education completed and human gender (Jiwa) at undergraduate level, labor force participation rate (TPAK), development index (HDI) and economic growth. Research findings show that education has a significant effect on economic growth. The labor force participation rate has a negative effect on economic growth. The human development index has a significant effect on economic growth. Education, labor force participation rate, human development index simultaneously have a significant effect on economic growth in Surakarta Residency. Policy implications based on the findings, it is recommended that the Regency/Municipal Government emphasize strategies for improving the quality of education and HDI.